OCCUPATIONAL SAFETY AND HEALTH IN SELECTED COUNTRIES OF THE EUROPEAN UNION - Tomaszewski, J.; Ignaciuk, E.; Томашевски, Я.; Игнацюк, E. (Харьковский национальный автомобильно-дорожный университет, 2012)
The article gives some of the normative legal basics from EU documents and occupational safety solutions in selected EU countries. Selected examples of countries represent the states with which Poland maintains a long-term cooperation in this area. These countries constitute a new labour market for Polish citizens.
БЕЗОПАСНОСТЬ И ГИГИЕНА ТРУДА В НЕКОТОРЫХ СТРАНАХ ЕВРОПЕЙСКОГО СОЮЗА
ПРОФЕСІЙНА БЕЗПЕКА І ЗДОРОВ’Я У ВІДІБРАНИХ КРАЇНАХ ЄВРОСОЮЗУ
Keywords: community; union; treatise; directives; occupational safety; сообщество; трактат; директивы; безопасность работы; суспільство; об’єднання; договір; директиви; професійна безпека; 621.863.2